The literature review of Islamic performance measurement models at sharia banks in Indonesia - Marheni, Marheni; Falikhatun, Falikhatun (Universitas Islam Negeri (UIN) Walisongo Semarang, 2024)
Purpose - The purposive of study was to find out maqashid sharia performance measurement model in sharia banking.Method - This type of research was qualitative descriptive research using a systematic literature review approach with primary data sources coming from ISSN or E-ISSN journal literature. Systematic literature review or structured article review is the process of identifying, assessing and interpreting all available research evidence with the aim of comparison, outcomes and providing answers to research questions.Result - Maqashid sharia measurement model mostly used at Islamic banking finance is the Sharia Maqashid Index (SMI). Maqashid sharia has the meaning of a goal that has been determined by the sharia for the ultimate benefit of human. Implication - Innovation of a strategic model to see and measure banking performance, therefore conventional banks and Islamic banks have different systems.Originality - This research combines sharia social performance and sharia financial performance into a performance measurement model.